Managing mycotoxins in on farm swine feeds in the northeastern U.S. - Andersen, Megan (My University, 2020)
The purpose of this thesis is to explore the possible affect that mycotoxins have on the aspects of hog production in the northeast region of the United States. Analyzing the impact of the most prevalent mycotoxins on hog health can show how a mycotoxin binder can be a positive influence on hog health and producers’ pocket. Through profiles of both mycotoxins and commonly used binders it can be shown how these unseen toxins have a lengthy and costly harmful impact on the profitability of hog production if not effectively managed. Using a partial budget economic analysis approach, demonstrates how costs associated with mycotoxins can be mitigated. This study compares the economic impact of mycotoxins in swine feed rations that contain a binder on a regular basis verses rations including binders on an as needed basis. A literary review aspect of this thesis will look at how economic models can estimate the overall economic impact of mycotoxins in the hog and livestock industries.
Keywords: Mycotoxin; Feed; economic impact; hog health; model